Methodological overview of the study of well-being through the Australian National Church Life Survey - Pepper, Miriam (Mental health, religion & culture, 2015)
All papers in this special edition of Mental Health, Religion & Culture utilise data sets from the 2011 round of the Australian National Church Life Survey (NCLS). This paper presents a methodological overview of the NCLS, including data collection methods, survey instruments and demographic descriptions of church attender and leader data sets. The data sets have good national coverage and denominational diversity, although Pentecostals are under-represented. The data sets may be further affected by self-selection by participating churches; however, the content of the surveys is unlikely to have triggered self-selection biases at the level of individuals. The paper also provides details concerning the measurement of quality of life in the present collection, concentrating on the Personal Wellbeing Index (PWI) which is featured in four of the five empirical papers. Mean PWI scores for churchgoers and leaders were similar to the Australian populace at large, although there was greater variability among churchgoers. The domain of spirituality/religion makes a significant contribution to well-being in these Australian Christian sub-populations.